2019
DOI: 10.1177/2325967119835587
|View full text |Cite
|
Sign up to set email alerts
|

Game-Related Impacts in High School Boys’ Lacrosse

Abstract: Background: The rate of concussions in boys’ lacrosse is reported to be the third highest among high school sports in the United States, but no studies have described game-related impacts among boys’ lacrosse players. Purpose: To characterize verified game-related impacts, both overall and those directly to the head, in boys’ varsity high school lacrosse. Study Design: Cross-sectional study; Level of evidence, 3. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
(83 reference statements)
0
13
0
Order By: Relevance
“…To evaluate potential changes in game play associated with headgear use, chi-square tests were used to examine the proportion of impact mechanisms and penalties administered between headgear conditions. Consistent with prior research, 4 , 6 , 9 the distribution of impact mechanisms (eg, stick, ball, body, or ground) was compared by headgear condition. We included all penalties referenced in the US Lacrosse and NFHS girls’ lacrosse rule books 2 that were the result of the impact and also shown on video.…”
Section: Methodsmentioning
confidence: 92%
See 4 more Smart Citations
“…To evaluate potential changes in game play associated with headgear use, chi-square tests were used to examine the proportion of impact mechanisms and penalties administered between headgear conditions. Consistent with prior research, 4 , 6 , 9 the distribution of impact mechanisms (eg, stick, ball, body, or ground) was compared by headgear condition. We included all penalties referenced in the US Lacrosse and NFHS girls’ lacrosse rule books 2 that were the result of the impact and also shown on video.…”
Section: Methodsmentioning
confidence: 92%
“…We were especially interested if headgear resulted in an increased rate of those impacts directly striking the head. Caswell et al 4 reported that 48% of all impacts in girls’ high school lacrosse directly struck the head. Our findings are encouraging, as we found that fewer than one-third (25.5%) of impacts directly struck the head.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations